Risk of Seizures after Immunization with Vaccine in Children - Rahman, Md Mizanur; Fatema, Kanij (Bangladesh Journal of Child Health, 2020)
Adverse neurological event particularly seizure after vaccination is not uncommon. The most linked vaccines are Diphtheria, Pertussis and Tetanus toxoid (DPT), Measles, Mumps and Rubella (MMR) and other combination vaccines. It is documented that increased febrile seizure after DPT and MMR vaccine is due to increase febrile episodes precipitating seizure and it is time related. Concomitant administration of vaccines cause seizure due to synergistic effect of those vaccines. When these vaccines are given separately, the risk of seizure is decreased. These type of vaccines are MMR + varicella (MMRV), DTaP-HepB-IPV etc. Regarding etiology, genetic mutation is most important. Some genes are closely related to vaccine induced FS and afebrile seizure like SCN1A, SCN2A, IFI44L, PCDH19 etc. Other causes are endotoxin mediated endothelial damage, IL-1â production and non CNS infection. It is well evident that consequences of not giving vaccine are far more than the adverse events. So Vaccinations should be performed without contraindication in children with previous febrile and afebrile seizures with proper counseling. Bangladesh J Child Health 2020; VOL 44 (1) :40-47